2012
DOI: 10.1371/journal.pone.0032252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wind on the Rate of Heat Loss from Avian Cup-Shaped Nests

Abstract: Forced convection can significantly influence the heat loss from birds and their offspring but effects may be reduced by using sheltered micro-sites such as cavities or constructing nests. The structural and thermal properties of the nests of two species, the spiny-cheeked honeyeater ( Acanthagenys rufogularis ) and yellow-throated miner ( Manorina flavigula ), were measured in relation to three wind speeds. Nest dimensions differ between the two species, despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 48 publications
(66 reference statements)
5
32
2
Order By: Relevance
“…This was because smaller birds (typically passerines) tended to produce disproportionately wider and deeper nests with relatively thicker walls than the non-passerines. By contrast, cup dimensions describe the space occupied by the bird and eggs and can be unrelated to other nest dimensions (Crossman et al, 2011;Heenan and Seymour, 2012). In the present study, cup diameter was highly correlated with body mass and exhibited no effect of taxon such that larger birds have relatively narrower nest cup diameters than smaller birds.…”
Section: Discussioncontrasting
confidence: 59%
“…This was because smaller birds (typically passerines) tended to produce disproportionately wider and deeper nests with relatively thicker walls than the non-passerines. By contrast, cup dimensions describe the space occupied by the bird and eggs and can be unrelated to other nest dimensions (Crossman et al, 2011;Heenan and Seymour, 2012). In the present study, cup diameter was highly correlated with body mass and exhibited no effect of taxon such that larger birds have relatively narrower nest cup diameters than smaller birds.…”
Section: Discussioncontrasting
confidence: 59%
“…Nests were stored for at least a year at approximately room temperature and humidity before analysis. Detailed observations of the arrangement of elements within the nest and identification of key structural regions were based upon observations and previous studies (Heenan & Seymour 2012, Mainwaring et al 2014. Nests were conditioned prior to testing at 23°C, 50% RH for 2 weeks in an environmental chamber (Sanyo MLR-351H, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Nest dimensions differ between the species, despite the adults having similar body masses, although the nest conductance of both species nests is comparable. The study found that the rate of heat loss from nests increased in both species as wind speed increased and as a result of forced convection through the nest, incubating parents would be required to double their heat production to maintain a suitable microclimate within the nest (Heenan and Seymour 2012). Nestbox-breeding prothonotary warbler ( Protonotaria citrea ) pairs that nested early in the season, when ambient temperatures were low, preferentially selected those nestboxes which had the highest ambient temperatures.…”
Section: Environmental Adjustmentmentioning
confidence: 99%